Defensive patent strategies in the European pharmaceutical industry - Skļamina, Zane (Riga Graduate School of Law, 2019)
For the purposes of keeping their commercial activities as effective and successful as possible, pharmaceutical companies can be eager to use different defensive strategies to protect their inventions and investments. Therefore, the main purpose of this master thesis is to examine certain defensive patent strategies used in the pharmaceutical industry, focusing on the European Union, and consequently establishing what are the problems and advantages related to these strategies.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Pharmaceutical industry